Energy sufficiency for deep decarbonization: A modeling framework - Jingjing Zhang; Michelle Johnson-Wang; Nina Khanna; Max Wei; Bianka Shoai-Tehrani; Nan Zhou (Nexus)
ABSTRACT: This work explores the concept and modeling of energy sufficiency, differentiating it from energy efficiency. Both elements are vital to rethinking established systems of production and consumption in the face of energy crises and climate change. The developing field of energy sufficiency can potentially constrain energy use within planetary resources while meeting humanity’s needs. Current energy and climate models generally exclude energy sufficiency, however, or combine it with energy efficiency, obscuring its distinct benefits. Theoretical frameworks, such as avoid-shift-improve, lack clear definitions and boundaries between sufficiency and efficiency measures.This paper introduces the decentralization, right-sizing and reduction, utilization/timing and longevity, multifunctionality, substitution, and sharing (DRUMSS) framework to improve the modeling of energy sufficiency. DRUMSS provides steps for implementing sufficiency measures across demand-side sectors, identifying policy actions to achieve deep decarbonization. We present three case studies, from the United States, China, and France, to illustrate implementing the DRUMSS framework in diverse contexts. Broader context: Deep decarbonization requires a robust framework to model and realize energy sufficiency, which provides energy services that support global social foundations operating within ecological limits. Current models either exclude energy sufficiency or combine it with energy efficiency, obscuring its unique benefits. This paper introduces the decentralization, right-sizing and reduction, utilization/timing and longevity, multifunctionality, substitution, and sharing (DRUMSS) framework, which provides definitions and boundaries for modeling sufficiency. DRUMSS identifies ways to establish energy sufficiency and to estimate the associated climate mitigation potentials. The framework supports both the scientific study and practical application of energy sufficiency. Three international case studies describe practical actions and policy levers for furthering sufficiency. The DRUMSS framework requires interdisciplinary collaboration to augment the indicators and data needed to communicate the benefits of sufficiency measures.